Towards Formalizing OO Models: A Case Study - Meng, Yew Kok; Bulbul, Helena; Hj. Yaacob, Mashkuri (Malaysian Journal of Computer Science, 2000)
Object Oriented System Development (OOSD) is gaining vast popularity among the software developers and researchers. However, the main challenge is to build a system which is reliable and less error-prone. The application of graphical informal Object Oriented (OO) technique for developing an OO system lacks validity checking though it can represent the system with more clarity. On the other hand, formal specification can facilitate the development of a correct implementation through automated reasoning techniques. The incorporation of formal specification together with informal technique helps in building complex and safety critical system. In this paper, we analyzed a case study system applying both formal and informal techniques. The informal technique for developing object model is Object Modeling Technique (OMT), the notation used is of Unified Modeling Language (UML) and the formal specification language used is Object-Z.